THE EFFECT OF COLLABORATIVE WRITING TECHNIQUE ON THE STUDENTS’ ABILITY IN WRITING RECOUNT TEXT AT SMP MUHAMMADIYAH 56 BINJAI - Ningsih, Agustina; Siregar, Nurmaliana Sari (Faculty of Tarbiyah nad Teacher Training, 2023)
This research was conducted to know the effectiveness of applying Collaborative Writing Technique on the students’ writing ability in writing recount text which was observed and analyzed at SMP Muhammadiyah 56 Binjai in Academic Year 2022/2023. The method used was quantitative research by using the experimental research design. The population of this study was eighth grade students of SMP Muhammadiyah 56 Binjai. In taking the sample of this research, the researcher took some students in each classes as the sample used and divided into 2 classes, experimental and controlled class. There were 22 students in the experimental and 22 students in controlled class. The researcher taught by using Collaborative Writing Technique in the experimental class and taught by using lecturing method in controlled class. The researcher used pre-test, treatment, and post-test. It shows that (Null Hypothesis) is rejected and (Alternative Hypothesis) is accepted. Unfortunately, by the Criterion of Minimum Standard (KKM) is 75 while the average score is 75.91 in experimental class. The increasement of score is only 0.91. So, there is no significant effect of using collaborative writing technique on the students’ ability in writing recount text at SMP Muhammadiyah 56 Binjai in academic year 2022/2023.